Acellular Dermal Matrix–sparing Direct-to-implant Prepectoral Breast Reconstruction: A Comparative Study Including Cost Analysis. Issue 2 (February 2020) - Viezel-Mathieu, Alex; Alnaif, Nayif; Aljerian, Albaraa; Safran, Tyler; Brabant, Gordon; Boileau, Jean-François; Dionisopoulos, Tassos
Abstract : Introduction: Refined mastectomy techniques, the advent of new technologies and materials such as acellular dermal matrix (ADM), cohesive gel silicone implants, and intraoperative tissue perfusion analysis, have fueled a resurgence in prepectoral breast reconstruction. This article aims to compare an immediate direct-to-implant prepectoral ADM-sparing approach with the traditional subpectoral 2-stage immediate reconstruction. A cost analysis within a Canadian-run single-payer system is also presented. Methods: A retrospective 2-group comparative chart review study was performed (June 2015–January 2017) to identify all patients who underwent prepectoral direct-to-implant breast reconstruction using an ADM-sparing technique. The comparison group consisted of patients having undergone traditional 2-stage subpectoral reconstruction with ADM. All countable variables were included in the cost analysis, which was performed in Canadian dollars. Results: A total of 77 patients (116 reconstructed breasts) were included. Both the prepectoral and subpectoral groups were comparable in size, demographics including age, diabetic and smoking status, and receiving neoadjuvant chemotherapy and postmastectomy radiotherapy. Patients having undergone direct-to-implant prepectoral reconstruction benefited from fewer follow-up visits (3.8 vs 5.4, respectively) and from less complications (24.7% vs 35.6%, respectively) including animation deformity. In addition, direct-to-implant prepectoral reconstruction costs 25% less than the 2-stage subpectoral reconstruction when all associated costs were considered. Conclusion: Prepectoral implant placement avoids many of the disadvantages of the traditional 2 stage subpectoral reconstruction, including pectoralis muscle dissection, animation deformity, and multiple surgeries. As the first comparative cost analysis study on the subject, our ADM-sparing direct-to-implant prepectoral reconstruction method costs 25% less than the traditional 2-stage subpectoral reconstruction with a comparable complication profile.